OPTIMISASI PELETAKAN DAN SIZING DISTRIBUTED GENERATION (DG) MENGGUNAKAN TWO LAYER PARTICLE SWARM OPTIMIZATION (TLPSO) - Arfah Z, Efrita (JURNAL TEKMAPRO, 2013)
ABSTRAKTwo Layer Particle Swarm Optimization (TLPSO) untuk optimisasi peletakan dan sizing DG.Distributed Generation (DG) merupakan pembangkit tersebar dengan tujuan menekan losses daya riil pada sistem. Data yang digunakan pada sistem ini adalah 30 bus IEEE.Â TLPSO yang merupakan perkembangan dari PSO terbukti lebih unggul di bandingkan dengan PSO.TLPSO mampu menurunkan losses sebesar 57.3%sedangkan PSO sebesar 51.11%.dibandingkan dengan sebelum peletakan DG. Losses daya riilÂ setelah peletakan DG dengan optimisasi TLPSO turun sebesar 12.6% dibandingkan PSO.Kata kunci: Distributed generation (DG), peletakan dan sizing optimal, Two Layer Particle Swarm Optimization (TLPSO)ABSTRACTTwo Layer Particle Swarm Optimization (TLPSO) for laying and sizing optimization DG.Distributed Generation (DG) is the power spread with the aim of suppressing the real power losses in the system. The data used in this system is the IEEE 30 bus. TLPSO which is the development of PSO is shown to be superior in comparison with PSO.TLPSO able to reduce losses by 57.3% and amounted to 51.11% of PSO. Compared with before laying DG.Real power losses after laying the optimization TLPSO DG decreased by 12.6% compared to PSO.Keywords: Distributed generation (DG), placement and optimal sizing, Layer Two Particle Swarm Optimization (TLPSO)